2021
DOI: 10.1186/s12935-021-01930-y
|View full text |Cite
|
Sign up to set email alerts
|

HHLA2 predicts better survival and exhibits inhibited proliferation in epithelial ovarian cancer

Abstract: Purpose The role of HHLA2, a new immune checkpoint ligand, is gradually being elucidated in various solid tumours. However, its role in ovarian cancer remains unclear; thus, its expression profile and clinical significance in ovarian cancer must be examined. Methods We performed immunohistochemistry to examine HHLA2 expression in 64 ovarian cancer tissues and 16 normal ovarian tissues. The relationships between HHLA2 expression and clinicopathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“… 22 The overexpression of HHLA2 inhibited cell proliferation of ovarian cancer. 19 The observed promoted effect of HHLA2 on PTC cells provides a view that the inhibition of HHLA2 might be a novel therapeutic strategy of PTC treatment.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“… 22 The overexpression of HHLA2 inhibited cell proliferation of ovarian cancer. 19 The observed promoted effect of HHLA2 on PTC cells provides a view that the inhibition of HHLA2 might be a novel therapeutic strategy of PTC treatment.…”
Section: Discussionmentioning
confidence: 92%
“…For instance, in epithelial ovarian cancer, HHLA2 behaves as a prognostic predictor associated with tumor differentiation and improved survival of patients. 19 In hepatocellular carcinoma, the co-expression of HHLA2 and PD-L1 was infrequent, but the overexpression of HHLA2 showed significant prognostic value. 20 However, the overall survival rate of enrolled patients in the present study was slightly different from previous data, 21 which might be a result of the relatively small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicated that overexpression of HHLA2 in tumour cells was associated with unfavorable clinical outcomes and shorter survival rate in patients with prostate cancer, 26 neuroendocrine tumours, 27 hepatocellular carcinoma, 28 , 29 , 30 lung adenocarcinoma, 31 , 32 , 33 , 34 gastric cancer, 35 oral squamous cell carcinoma, 36 bladder urothelial carcinoma, 37 intrahepatic cholangiocarcinoma, 38 colorectal carcinoma, 39 , 40 osteosarcoma, 41 and triple negative breast cancer. 17 On the contrary, HHLA2 was a protective factor predicting low mortality rate in patients with pancreatic cancer, 14 , 42 , 43 epithelial ovarian cancer, 44 malignant glioma, 45 and recurrent or unresectable advanced gastric cancer. 46 The discrepancy could plausibly result from the dual role of HHLA2 as both inhibitory and stimulatory immune checkpoint that switch to predominant in different cancer types, further affecting the clinical outcome.…”
Section: Role Of Hhla2 In Cancer Developmentmentioning
confidence: 96%
“… Prostate cancer 2021 Patient tumour samples, N = 239 Tumour cells High HHLA2 expression was an independent prognostic predictor for prostate cancer, and was negatively correlated with CD TILs 26 Neuroendocrine tumours 2021 Patient tumour samples, N = 37 Tumour cells High HHLA2 expression was correlated with high tumour grade and metastasis 27 Colorectal cancer 2021 Patient tumour samples, N = 214 Tumour cells HHLA2 expression was low in colorectral cancer and appeared to have no influence on clinical outcomes. 40 Hepatocellular carcinoma 2021 Patient tumour samples, N = 205 Peri-tumour region of HCC tissues HHLA2 expression in the peri‑tumour region was an independent prognostic factor for OS, and was negatively correlated with PD-L1 28 Patient tumour samples, N = 55 Tumour cells Higher expression of HHLA2 protein was associated with advanced cancer stage, tumour differentiation, and invasion of adjacent structures 29 Patient tumour samples, N = 202 Tumour cells HHLA2 level was a independent worse prognostic factor and affected the tumour microenvironment 30 Epithelial ovarian cancer 2021 Patient tumour samples, N = 64 Tumour cells HHLA2 was correlated with high CD TIL levels and tumour differentiation; and predicted improved survival in ovarian cancer 44 Lung adenocarcinoma 2021 Patient tumour samples, N = 62 Tumour cells HHLA2 expression was an prognostic factor for PFS, and was positively correlated with EGFR overexpression …”
Section: Role Of Hhla2 In Cancer Developmentmentioning
confidence: 99%
“…Among women, ovarian cancer (OC) is the fifth leading cause of tumor-associated deaths and is correlated with the highest mortality rate among gynecological malignancies worldwide ( Wang et al, 2021a ; Seborova et al, 2021 ). Surgery and postoperative platinum-based chemotherapy are the major treatments of OC, according to guidelines of the National Comprehensive Cancer Network (NCCN) ( Xu et al, 2021a ). Even though surgery and chemotherapy can increase survival, the 5-year survival rate of OC patients remains extremely low ( Liu et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%